A surge in anti-dsDNA titer predicts a severe lupus flare within six months. (March 2014) - Pan, N; Amigues, I; Lyman, S; Duculan, R; Aziz, F; Crow, MK; Kirou, KA
Objective: Rising anti-double-stranded (ds) DNA titers have been shown by some, but not all, studies to be predictive of disease flares in systemic lupus erythematosus (SLE). We hypothesized that a rapid and substantial rise in anti-dsDNA titer (anti-dsDNA surge) would be a good predictor of a clinically important SLE flare. Methods: A matched case-control study was conducted in an academic rheumatology practice setting. Our primary endpoint was the occurrence of a severe SELENA-SLEDAI (SS) flare within six months of an anti-dsDNA surge, and secondary endpoints were mild/moderate SS flares, as well as BILAG A and B renal flares. Cases were identified as those patients whose disease course included a surge of anti-dsDNA, defined as an increase of anti-dsDNA titer by the Crithidia luciliae immunofluorescence (CLIF) assay from 0 to 3+/4+, or from 1+ to 4+, within a period of less than 12 months. The date of the anti-dsDNA surge was defined as Day 0. Two control SLE patients were identified for each case and were matched for age, sex, race, and visit date closest to case Day 0, but without an anti-dsDNA surge. Logistic regression models were used to detect associations between anti-dsDNA surges and severe SS flares. Result: A higher proportion of cases, compared to controls, experienced a severe SS flare within six months of Day 0 (OR 6.3 (95% confidence intervals 2.0–19.9), p = 0.02). Associations with all flares and hospitalizations for flares were also observed. However, an anti-dsDNA surge was not predictive of a renal flare. Conclusion: An anti-dsDNA surge predicts the subsequent development of a severe SS flare within six months. Physicians should closely monitor such patients and treat promptly at the first sign of clinical activity.